2020
DOI: 10.1109/access.2020.3009481
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Objective Optimal Gearshift Control for Multispeed Transmission Electric Vehicles

Abstract: Electric vehicles are being increasingly adopted worldwide to support the sustainable development of society. However, various technologies that are related to electric vehicles still require further investigation. In this study, we consider a gearshift control architecture that combines offline trajectory planning and online control for improved shifting in multispeed transmission electric vehicles. For gearshift trajectory planning, we establish a dynamic model and apply the multi-objective optimization Rada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…For four different positions of the piezoelectric actuator, the PID control and FxLMS control algorithm can excellently reduce the single frequency vibration of the system at 4 times the engagement base frequency [20]. For position 1, at the target frequency, the vibration can decrease by about 3 dB by the PID control.…”
Section: Optimization Of Piezoelectric Actuator Operationmentioning
confidence: 95%
“…For four different positions of the piezoelectric actuator, the PID control and FxLMS control algorithm can excellently reduce the single frequency vibration of the system at 4 times the engagement base frequency [20]. For position 1, at the target frequency, the vibration can decrease by about 3 dB by the PID control.…”
Section: Optimization Of Piezoelectric Actuator Operationmentioning
confidence: 95%
“…This approach enables precise and efficient control optimization with only a few experiments [22], [23]. Previous studies have applied PILCO to different engineering disciplines, including an autopilot underwater vehicle control problem [24], [25], constant force control of a robot surface [26], autonomous optimization of PID parameters in the control of a flight attitude simulator [27], and experiments on a planetary gear transmission shift console frame [28]. These studies have shown that PILCO can obtain the ideal controller strategy for the gearbox with a relatively small number of experiments.…”
Section: Introductionmentioning
confidence: 99%
“…As a typical algorithm of direct method, the pseudospectral method mainly includes three types: the Gauss pseudospectral method, the Legendre pseudospectral method, and the Radau pseudospectral method. Recently, the pseudospectral method has attracted increasing interest due to fast convergence and high precision, and it is widely used in many fields: shifting process control for transmission, 17,18 vehicle economical driving, 19,20 and spacecraft trajectory optimization. 21 The pseudospectral method discretizes the state and control variables and approximates them through the Lagrange interpolation base function.…”
Section: Introductionmentioning
confidence: 99%